Effects of Corporate Business Leadership Strategies Regarding Effective Humanitarian Crisis Management - Dieuveille, Lesly (Digital Repository of Theses, 2025)
This dissertation thoroughly investigates the profound impact of corporate leadership strategies on humanitarian crisis management, with a keen focus on the pivotal roles of visionary, collaborative, and strategic leadership. Effective leadership is the cornerstone for ensuring timely and efficient responses in the face of increasingly frequent and complex humanitarian crises, such as natural disasters, armed conflicts, and pandemics. The research was rigorously conducted in the Democratic Republic of the Congo (DRC), an area grappling with significant humanitarian challenges, rendering it an ideal setting for this study. Using a quantitative method approach, the researcher meticulously gathered data from corporate leaders, humanitarian leaders, humanitarian aid workers, mid-level employees, and field-level staff to comprehensively assess leadership effectiveness during crises. The findings underscore the indispensable nature of visionary leadership for setting a clear direction and maintaining focus while acknowledging the challenges in translating vision into actionable steps. Collaborative leadership emerges as a foundation for enhancing communication and teamwork among various stakeholders, even as leaders confront difficulties managing conflicts and ensuring that all voices are heard. Strategic leadership is revealed as playing a vital role in planning and resource allocation, yet leaders grapple with the delicate balance between immediate crisis demands and long-term goals. The study highlights the recurrent challenges faced by corporate leaders across all three leadership styles, such as balancing priorities, engaging stakeholders, and adapting to rapidly changing circumstances. These challenges, while daunting, are a testament to the resilience and adaptability of leaders in crisis situations. Overall, the research emphatically underscores the critical importance of integrating visionary, collaborative, and strategic leadership approaches to ameliorate crisis management outcomes. This dissertation furnishes invaluable insights for corporate leaders, policymakers, and humanitarian organizations, emphatically underscoring the imperative need for effective leadership in managing humanitarian crises. The findings ardently aim to contribute to the development of more adaptive and responsive leadership strategies that can better address the complexities of future humanitarian challenges. The call for future research is not just a suggestion but a passionate plea to delve deeper into the evolving nature of leadership in crisis management and its implications for global humanitarian efforts.